2020
DOI: 10.1111/nhs.12736
|View full text |Cite
|
Sign up to set email alerts
|

Gender, exercise, and health: A life‐course cross‐sectional study

Abstract: The purpose of this study is to explore relationships between the practice of exercise, gender, and health, from adolescence to old age, testing the magnitude of gender differences throughout the life cycle in the practice of exercise of Spanish people. A cross‐sectional study with 4,575 women and 4,334 men, aged 13–85 years, was conducted. The participants were assessed on the weekly hours they dedicated to the practice of exercise, masculine/instrumental and feminine/expressive traits, mental health symptoma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 39 publications
0
6
0
Order By: Relevance
“…Literature [ 21 ] in sports health management gives full play to the advantages of ASP technology and B/S structure technology, and establishes a scientific, practical, simple, and extensible sports health management platform based on Web database technology. Literature [ 22 ] proposed that when creating web pages and developing web database pages, first we should establish some static hypertext markup language (HTML) pages that support the whole web file system. We can also use InterDev to add files to them.…”
Section: Related Workmentioning
confidence: 99%
“…Literature [ 21 ] in sports health management gives full play to the advantages of ASP technology and B/S structure technology, and establishes a scientific, practical, simple, and extensible sports health management platform based on Web database technology. Literature [ 22 ] proposed that when creating web pages and developing web database pages, first we should establish some static hypertext markup language (HTML) pages that support the whole web file system. We can also use InterDev to add files to them.…”
Section: Related Workmentioning
confidence: 99%
“…Men’s androgen levels are higher than women’s, making them likely to be excited by online sensory stimulation; therefore, they tend to use the internet and mobile apps for longer periods than women[ 30 ]. Some studies have found that men are better than women at spatial perception[ 31 ], hand-eye coordination[ 32 ], and competitive activities[ 33 ]. Therefore, they generally prefer sports, technology, politics, and other topics on social media[ 34 ], whereas women are more inclined to share family and personal details and other content on social media[ 35 ].…”
Section: Discussionmentioning
confidence: 99%
“…Research has shown that exercise positively affects the perception of health status in people 18 . The current study also highlighted a significant relationship between exercise frequency and self-rated general health.…”
Section: P R O V I S I O N a L L Ymentioning
confidence: 99%